Analisis Kepuasan Mahasiswa Terhadap Layanan Akademik Dengan Metode Servqual dan Importance Performance Analysis - I Made Dwi Wira Ardana; I Nengah Rata Artana; Ida Bagus Kurniawan (Jurnal Manajemen dan Bisnis Kreatif)
A B S T R A C T The purpose of this study is to analyze student satisfaction with XYZ University academic services. The instrument in this study was a questionnaire compiled based on the dimensions of the quality of the servqual method, namely tangibles, reliability, responsiveness, assurance and empathy with 4 Likert scales. The sampling method uses the slovin approach, the sampling technique used is proportional sampling. Servqual method (service quality) is used to measure the service gap. To display the factors that determine satisfaction and service factors must be improved, the Importance Performance Analysis (IPA) method is used. From the results of the calculation of the Servqual score, an average gap value of -0.29 indicates a gap in the quality of academic services with what is expected by students, an average conformity level of 91.28% is in very suitable criteria (80 - 100%) indicating significantly XYZ University's academic service quality is close to what is expected by students, but still needs to be improved. From the IPA analysis, there are 18 academic service attributes that are considered important by students.